2016
DOI: 10.3390/s16081288
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Imaging Using Flexible Endoscopy for Laryngeal Cancer Detection

Abstract: Hyperspectral imaging (HSI) is increasingly gaining acceptance in the medical field. Up until now, HSI has been used in conjunction with rigid endoscopy to detect cancer in vivo. The logical next step is to pair HSI with flexible endoscopy, since it improves access to hard-to-reach areas. While the flexible endoscope’s fiber optic cables provide the advantage of flexibility, they also introduce an interfering honeycomb-like pattern onto images. Due to the substantial impact this pattern has on locating cancero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 24 publications
0
51
0
Order By: Relevance
“…In particular, HSI has started to achieve promising results in the recent years with respect to cancer detection through the utilization of cutting-edge machine-learning algorithms [4,[19][20][21]. Several types of cancer have been investigated using HSI including both in vivo and ex vivo tissue samples, such as gastric and colon cancer [22][23][24][25], breast cancer [26,27], head and neck cancer [28][29][30][31][32][33], and brain cancer [34][35][36], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HSI has started to achieve promising results in the recent years with respect to cancer detection through the utilization of cutting-edge machine-learning algorithms [4,[19][20][21]. Several types of cancer have been investigated using HSI including both in vivo and ex vivo tissue samples, such as gastric and colon cancer [22][23][24][25], breast cancer [26,27], head and neck cancer [28][29][30][31][32][33], and brain cancer [34][35][36], among others.…”
Section: Introductionmentioning
confidence: 99%
“…The in vivo application in combination with automated imaging analysis would make it possible in the future to display the results into a postprocessed image guiding the surgeon during surgery in real time. Such an application has already been introduced for hyperspectral imaging using flexible endoscopy for laryngeal cancer detection …”
Section: Discussionmentioning
confidence: 99%
“…The second clinical focus of using intraoperative HSI has been to guide tumour resection. The feasibility of using HSI as a diagnostic technique for cancer has been comprehensively evaluated in multiple preclinical animal models and several recent studies have also demonstrated its use in assessing tumour margins in ex vivo tissue in the operating room [9][10][11][12][13][14][15][16][17][18][19][20][44][45][46][47][48]. Fewer studies have reported the in vivo use of HSI during surgery but several groups have used HSI to highlight subtle changes in exogenous fluorescence [53,54,69].…”
Section: Intraoperative In Vivo Hsi Functionsmentioning
confidence: 99%
“…The ability to quantitatively measure oxygenation levels in tissue has been tested in various pathologies and clinical contexts, including; peripheral vascular disease , retinal eye disease , diabetic foot disease and wound healing . Numerous groups have also published work demonstrating the effectiveness of using HSI for cancer detection . With the development of high‐resolution and fast frame rate multispectral and HSI cameras, enabling the capture of a rich imaging dataset at a video rate, these imaging methods offer great potential for real‐time non‐invasive tissue characterization and surgical guidance .…”
Section: Introductionmentioning
confidence: 99%